2015
DOI: 10.18051/univmed.2015.v34.149-158
|View full text |Cite
|
Sign up to set email alerts
|

Frequent coconut milk intake increases the risk of vascular disease in adults

Abstract: <p>Background <br />Coconut milk is an essential ingredient of the Indonesian cuisine. In view of its saturated fatty acid content, coconut milk has frequently been blamed as a cause of cardiovascular disease. The objective of this study was to determine any association between coconut milk intake and vascular disease among adults.<br /><br />Methods<br />A cross-sectional study was conducted in 2011-2012 on adults aged 25-65 years. Self-reported health and nutritional data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…It is not viable, however, to conclude that high coconut milk intake will lead to CHD as DP1 in this study was based on the combination of several other foods groups including fast foods, snacks, and fat spread. Nonetheless, a previous study reported that frequent consumptions of coconut milk of > 3 times per week increased risk of vascular disease 56 . In contrast, an earlier study found that SFA intake, including coconut, was not a predictor of CHD among coconut-consuming Minangkabau in West Sumatra Indonesia 57 .…”
Section: Modelmentioning
confidence: 97%
“…It is not viable, however, to conclude that high coconut milk intake will lead to CHD as DP1 in this study was based on the combination of several other foods groups including fast foods, snacks, and fat spread. Nonetheless, a previous study reported that frequent consumptions of coconut milk of > 3 times per week increased risk of vascular disease 56 . In contrast, an earlier study found that SFA intake, including coconut, was not a predictor of CHD among coconut-consuming Minangkabau in West Sumatra Indonesia 57 .…”
Section: Modelmentioning
confidence: 97%
“…This coconut milk is made from grated coconut meat, then mixed with water and squeezed. Coconut milk contains water, protein, and fat, which is quite high [18] and coconut milk will increase the occurrence of plaque in the blood vessels, which can further lead to hypertension [19]. The pathophysiology of fat metabolism that causes hypertension is started from lipoproteins as lipid carriers circulating in the body and carried into muscle cells, fat, and other cells.…”
Section: Determinants Of Hypertension Proxy In Kawatuna Urban-villagementioning
confidence: 99%
“…Another study found that supplementation of coconut milk significantly reduced LDL cholesterol levels and increased HDL cholesterol levels [45]. Therefore it may be stated that intake of coconut milk is not a risk factor of vascular disease [46].…”
mentioning
confidence: 99%